About Noise in Religious Context: Religious Communication Perspective - Soizick Crochet (CoverAge: Journal of Strategic Communication, 2016)
The World Health Organization has confirmed the severe health consequences of noise pollution. Paradoxically, conflicts and regulations seem more common not where noise pollution reaches the worse levels. As a new “trend” in health related issues, it seems to be more seriously taken in the West, arguably a great deal quieter than less developed countries. In the latter, the battle has been picked up by the more affluent or middle income segments of the population. But when it comes to limit noisy religious signals, they often meet strong resistance, specially in interfaith contexts, but also in Indonesia, among members of the same religion. In order to overcome cultural and political factors, they are sometimes turning to a public health narrative. It implies a shift in sensory and sleeping patterns, not unlike pre-industrial Europe, but relatively new for these regions.